Multiplex analysis of cytokines in the cerebrospinal fluid of dogs after ischemic stroke reveals elevations in chemokines CXCL1 and MCP-1 - Barber, Renee M.; Platt, Simon R.; De Risio, Luisa; Barber, Jamie; Robinson, Kelsey R. (Frontiers in Veterinary Science, 2023)
Introduction: Neuroinflammation that occurs in the brain after stroke has been shown to be important to disease pathogenesis and outcomes. The aim of this study was to evaluate a large number or pro- and anti-inflammatory cytokines in dogs with clinically-confirmed, naturally occurring stroke. Materials and methods: Fifteen dogs with a clinical diagnosis of ischemic stroke and ten healthy control dogs were included in the study. A multiplex immunoassay was utilized to evaluate cerebrospinal fluid for GM-CSF, IFN-γ, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10, IL-15, IL-18, IP-10, CXCL1, MCP-1 and TNF-α. Results: Mean concentrations of CXCL1 (stroke-436 pg/ml, control-267 pg/ml, p=0.01) and MCP-1 (stroke-196 pg/ml, control-66 pg/ml, p=<0.0001) were significantly elevated in dogs with stroke when compared with control dogs. Location and type of infarct, duration of clinical signs, and use of anti-inflammatory medications were not associated with differences in cytokine concentration. Discussion: CXCL1 and MCP-1 may play a role in naturally occurring canine stroke and represent targets for future research.